GAMBARAN PEMERIKSAAN KEHAMILAN PADA ANTENATAL CARE DI TEMPAT PELAYANAN KESEHATAN DI KABUPATEN BREBES TAHUN 2010 - Saraswati, Lintang Dian; Ginanjar, Praba (Kesmas Indonesia: Jurnal Ilmiah Kesehatan Masyarakat, 2011)
ABSTRACT Antenatal Care (ANC) is a service provided to pregnant women by health workers to maintain pregnancy. Coverage of complete antenatal care visits in Brebes remains below the standard. This possibly related to the completeness of pregnancy examination privided in Brebes District.. This study aimed to describe pregnancy examination in the ANC in Brebes District. This was a descriptive study with rapid survey design and multistages sampling method. Research subjects were 210 mothers with 0-4 months baby. The results showed the majority of pregnant women in Brebes conceive a healthy reproductive age, low education level, and unemployed. Complete ANC (K4) coverage in January-May 2010 is 26.67%. Proportion of trimester visit I-III tends to decrease. Examination of pregnancy has not been fully compliant the 7T standard, including blood pressure measurements, giving of Fe tablets, urine and blood laboratory tests, the completeness of TT immunization, fundal height measurements, as well as pregnancy counseling. District Health Office Brebes is expected to improve the performance of health workers and health care facilities on pregnancy examination as an effort to improve Maternal and Child Health to improve antenatal care visits.  Key words : antenatal care, complete antenatal care Kesmasindo. Volume 4,( 1) Januari 2011, hlm. 24-37